Primary cardiac atrial sarcomas. Report of two histologically different cases and review of the literature - Püsküllüoglu, Mirosława; Kruczak, Anna; Mularz, Katarzyna; Rozmus, Magdalena; Harazin-Lechowska, Agnieszka; Pietruszka, Agnieszka; Jaworska, Justyna; Ziobro, Marek; Grela-Wojewoda, Aleksandra; Ryś, Janusz (Polish Journal of Pathology, 2021)
Primary cardiac sarcomas are extremely uncommon. We report two patients with primary cardiac atrial sarcomas: a case report of a 34-year old woman with intimal sarcoma of the left atrium and a case report of a 30-year old man with synovial sarcoma of the right atrium. Clinicopathological and differential diagnosis with a discussion regarding the role of molecular studies is presented.